2019
DOI: 10.4149/av_2019_210
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of TNF-α and IL-10, IL-12, IL-17 genes and association with torque teno virus infection post hematopoietic stem cell transplantation

Abstract: Little is known about the role of genetic variation in the genes for cytokines and susceptibility to viral infection especially torque teno virus (TTV) following allogeneic hematopoietic stem cell transplantation. In this study, the association between interleukin-12, interleukin-17, interleukin-10 (IL-12,-17,-10) and tumor necrosis factor α (TNF-α) polymorphisms was evaluated in patients with TTV infection who underwent allogeneic hematopoietic stem cell transplantation from South of Iran. The single nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…The present investigation is the first to evaluate to what extent the kinetics of TTV DNA levels following KT are influenced by SNPs in genes coding for PRRs (TLR3, TLR9 and CD209), ILs and cytokines (IL-12B, IL-17, IL-10, TNF), IFN-λ3 (IL-28B) and the costimulatory receptor CTLA-4). These candidate SNPs were chosen on the basis of prior studies performed in the HSCT population (Ramzi et al, 2019;Ramzi et al, 2021) or due to their well-established involvement in other viral infections in SOT recipients (Redondo et al, 2022d). We found no clear association between any of the SNP genotypes considered and various parameters reflecting viral kinetics after transplantation, such as mean and peak DNA levels or AUCs for plasma TTV DNAemia during discrete periods, or absolute increments from baseline.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The present investigation is the first to evaluate to what extent the kinetics of TTV DNA levels following KT are influenced by SNPs in genes coding for PRRs (TLR3, TLR9 and CD209), ILs and cytokines (IL-12B, IL-17, IL-10, TNF), IFN-λ3 (IL-28B) and the costimulatory receptor CTLA-4). These candidate SNPs were chosen on the basis of prior studies performed in the HSCT population (Ramzi et al, 2019;Ramzi et al, 2021) or due to their well-established involvement in other viral infections in SOT recipients (Redondo et al, 2022d). We found no clear association between any of the SNP genotypes considered and various parameters reflecting viral kinetics after transplantation, such as mean and peak DNA levels or AUCs for plasma TTV DNAemia during discrete periods, or absolute increments from baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the relative contribution of the innate system—and its genetic determinants—has not been characterized so far. To our knowledge only three previous works have analyzed the impact of genetic polymorphisms on TTV replication in HSCT recipients (with two studies from the same group) and people living with human immunodeficiency virus (HIV) ( Prasetyo et al, 2015 ; Ramzi et al, 2019 ; Ramzi et al, 2021 ). Ramzi et al (2019) ; Ramzi et al (2021) found a correlation between SNPs in IL10 , CTLA4 and TNF genes and TTV infection in allogeneic HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations